2003
DOI: 10.1007/s00394-003-0387-5
|View full text |Cite
|
Sign up to set email alerts
|

The status of plasma homocysteine and related B-vitamins in healthy young vegetarians and nonvegetarians

Abstract: Vitamin B-12 intake and mean plasma vitamin B-12 concentration were lower for vegetarian subjects than for nonvegetarian subjects, leading to an increase in plasma homocysteine concentration. Vitamin B-6 and folate had little effect on plasma homocysteine concentration when individuals had adequate vitamin B-6 and folate status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 29 publications
4
42
0
1
Order By: Relevance
“…Our data also showed that the vegetarians had a significantly higher level of homocysteine than omnivores in both men and women. This result is similar to that of previous studies on vegetarians carried out in Taiwan and elsewhere (Krajèovioèvá-Kudláèková et al, 2000;Hung et al, 2002;Herrmann et al, 2003;Huang et al, 2003;Su et al, 2006). In experimental studies, homocysteine has been shown to stimulate vascular smooth muscle cells to proliferate and to synthesize collagen, which is a hallmark of atherogenesis.…”
Section: Conventional Cardiovascular Risk Factorssupporting
confidence: 90%
See 1 more Smart Citation
“…Our data also showed that the vegetarians had a significantly higher level of homocysteine than omnivores in both men and women. This result is similar to that of previous studies on vegetarians carried out in Taiwan and elsewhere (Krajèovioèvá-Kudláèková et al, 2000;Hung et al, 2002;Herrmann et al, 2003;Huang et al, 2003;Su et al, 2006). In experimental studies, homocysteine has been shown to stimulate vascular smooth muscle cells to proliferate and to synthesize collagen, which is a hallmark of atherogenesis.…”
Section: Conventional Cardiovascular Risk Factorssupporting
confidence: 90%
“…In Taiwanese vegetarians, the intake and mean plasma concentration of vitamin B 12 were lower than in omnivores, which leads to an increase in plasma homocysteine concentration. Furthermore, vitamin B 6 and folate have little effect on plasma homocysteine concentration when individuals have an adequate vitamin B 6 and folate status (Huang et al, 2003). In The Swiss Heart Study, homocysteine-lowering therapy with folic acid, vitamin B 12 and vitamin B 6 significantly decreases the incidence of major events after percutaneous coronary intervention (Schnyder et al, 2002).…”
Section: Vitamin Supplementationmentioning
confidence: 99%
“…Before starting the experiments, all rats were acclimated to the facility for 5 d and given free access to water and a 25% casein diet. In the present study, seven experimental diets (A-G) differing in casein level (10,30, and 50%) and differing in methionine level together with or without glycine ϩ serine supplementation were used (Table 1). These diets were abbreviated as follows:…”
Section: Animals and Dietsmentioning
confidence: 99%
“…In contrast, sustained intakes of high protein diets did not alter plasma homocysteine concentration in some interventional studies ( 6 , 7 ). Several observational studies have shown that there was no significant correlation between plasma homocysteine concentration and protein intake ( 8 -11 ), whereas a significantly positive ( 12 ) or negative ( 13 ) correlation was found between the two variables in some studies. Thus, the results of previous human studies on the relationship between plasma homocysteine concentration and protein intake are not consistent, and it appears that a consensus has not yet been established.…”
mentioning
confidence: 97%